TNFAIP3 mutation causing haploinsufficiency of A20 with a hemophagocytic lymphohistiocytosis phenotype: a report of two cases - Nahid Aslani; Kosar Asnaashari; Nima Parvaneh; Mohammad Shahrooei; Maryam Sotoudeh-Anvari; Farhad Shahram; Vahid Ziaee (BMC, 2022)
Abstract Background A20 haploinsufficiency (HA20) is a newly introduced autosomal dominant autoinflammatory disorder, also known as Behcet's-like disease. Some of the most common symptoms of the disease are recurrent oral, genital, and/or gastrointestinal (GI) ulcers, episodic fever, musculoskeletal symptoms, cutaneous lesions, and recurrent infections. Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition of multi-organ failure due to excessive immune activation. HLH has been reported in a few HA20 patients. Herein, we report two children with the primary presentation of HLH, with a mutation in TNFAIP3, in favor of HA20. Case presentations Our first patient was a 4-month-old boy who presented with fever, irritability, pallor, and hepatosplenomegaly. Pancytopenia, elevated ferritin, and decreased fibrinogen levels were found in laboratory evaluation. He was diagnosed with HLH and was treated with methylprednisolone and cyclosporine. Two years later, whole exome sequencing (WES) indicated a mutation in TNFAIP3 at NM_001270507: exon3: c.C386T, p.T129M, consistent with A20 haploinsufficiency. Etanercept, a TNF inhibitor, was prescribed, but the parents were reluctant to initiate the therapy. The patient passed away with the clinical picture of cerebral hemorrhage. The second patient was a 3-month-old boy who presented with a fever and hepatosplenomegaly. Laboratory evaluation found pancytopenia, hyperferritinemia, hypoalbuminemia, hypertriglyceridemia, and hypofibrinogenemia. With the establishment of the HLH diagnosis, he was treated with etoposide, dexamethasone, and cyclosporine, and recovered. WES results revealed a heterozygous de novo variant of TNFAIP3 (c. T824C in exon 6, 6q23.3) that leads to a proline to leucine amino acid change (p. L275P). He was treated with etanercept and has been symptom-free afterward. Conclusions This report is a hypothesis for developing of the HLH phenotype in the presence of TNFAIP3 mutation. Our results provide a new perspective on the role of TNFAIP3 mutation in HLH phenotypes, but more extensive studies are required to confirm these preliminary results.